Exploring the diversity of butterflies (lepidoptera) at different elevations in genting highlands and the validity of graphium species in peninsular malaysia / Karen Chia Huey Min - Chia, Karen Huey Min (2014)
Butterflies play an ecological role as pollinators, prey, defoliators and herbivores. They are in abundant and diverse in many ecosystems. However, they are serves as indicators of ecosystem change and predict environmental alternation. This study was conducted to (1) compare the attractiveness of ten types of fruit bait and make recommendations on the most efficient fruit bait types for trapping butterflies in the South East Asian tropical forest; (2) investigate how butterfly diversity is related to elevation at Genting Highlands in Peninsular Malaysia; and (3) explore the phylogenetic relationships within Graphium and the validity of Pathysa. The bait trap is one of the most common methods used for trapping butterflies in the field and particularly for fruit feeding butterflies. The present study was conducted to determine the efficiency of traps baited with ten different fruit baits. Traps were baited with either: banana (Musa spp), chiku (Manikara sapota), citrus (Citrus aurantifolia), dragon fruit (Hyllocereus undatus), guava (Psidium guajava), papaya (Carica papaya), pineapple (Ananas comosus), rose apple (Syzygium malaccense), star fruit (Averrhoa carambola) and watermelon (Citrullus lanatus) at Ulu Gombak, Selangor, Malaysia. A total of 194 Nymphalids butterflies of 28 species were recorded in our study. Banana was found to be the most attractive bait trapping a total of 14 species of Nymphalids. Based on our study, we would recommend using banana for collecting butterfly in the South-East Asia tropics. Several previous studies indicate that butterfly diversity declines with elevation due to increasingly unfavourably environmental conditions and reduced vegetation. Here, we investigate how butterfly diversity is related to elevation at Genting Highlands in Peninsular Malaysia. A total of 2, 876 butterflies belonging to 214 species were collected from six sites of different elevation between January and December 2011. Nymphalidae (1599 individuals) was the most abundant family and Ypthima pandocuswas the most abundant species (718 individuals), followed by Eurema hecabe (194 individuals) and Leptosia nina (75 individuals). The highest diversity (118 species, H‟=3.882) was seen at low elevation (480 m a.s.l.) with declining species diversity at higher sites. The COI mtDNA barcodes for Graphium specimens from Museum of Zoology, University of Malaya and Jengka, Pahang was sequenced to test the utility of DNA barcoding for the identification of Graphium species. In addition, the sequences of 28S rRNA were used to examine, in conjunction with COI, phylogenetic relationships and investigate the validity of Pathysa and Parantocopsis as distinct genera. All species of Graphium possessed a distinctive cluster of DNA barcodes with the exception of the specimens originally identified as Graphium bathycles and Graphium chironides which shared DNA barcodes. Furthermore, the morphological identification of Graphium bathycles and Graphium chironides was ambiguous as the specimens overlapped for the diagnostic characters reported for each taxon. Moreover, the maximum parsimony trees of the COI and 28S rRNA showed a similar topology with Paranticopsis species forming a clade within a larger clade comprising the Pathysa species. In order for Pathysa to be a valid genus, at least three other clades within Graphium s.l. would also have to be raised as genera.